2019
DOI: 10.2478/s11686-019-00148-3
|View full text |Cite
|
Sign up to set email alerts
|

Genotyping by Sequencing of Acanthamoeba and Naegleria Isolates from the Thermal Pool Distributed Throughout Turkey

Abstract: Purpose The main goal of this study was genotyping of free-living parasites and sub-grouping of pathogenic or non-pathogenic amebae obtained from Turkey's thermal springs. In so doing, distribution and abundance of possible pathogenic or causative strain for humans, which are caused by Acanthamoeba and Naegleria strains, would be elaborated. The number of extensive studies on the general occurrence and distribution of parasitic strains is very high worldwide, but there has been a paucity of information with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In Turkey, Naegleria spp. was also found in much lower prevalence than Acanthamoeba ( 45 ). However, it is also claim that 92.9% of 70 environmental water specimens from parks in China were contaminated to Naegleria ( 46 ).…”
Section: Discussionmentioning
confidence: 93%
“…In Turkey, Naegleria spp. was also found in much lower prevalence than Acanthamoeba ( 45 ). However, it is also claim that 92.9% of 70 environmental water specimens from parks in China were contaminated to Naegleria ( 46 ).…”
Section: Discussionmentioning
confidence: 93%
“…was found in various water sources worldwide at 0.6%–60.9% all over the world, and 0.7–10% in Turkey. [ 26 , 34 , 35 ]. We conclude that Naegleria spp.…”
Section: Discussionmentioning
confidence: 99%
“…The most common genotypes, T4 (93.7%) and T2 (6.25%) were determined in the geothermal river in the southwest of Iran by Niyyati et al [ 46 ]. The most common T4 and T2, T3, T5, T11, T15 genotypes of Acanthamoeba were detected in environmental water samples in Turkey [ 34 , 47 50 ]. In the previous study T4 and T5 genotypes were reported in keratitis wild birds in İzmir [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…was found in various water sources worldwide at 0.6%-60.9% all over the world, and 0.7-10% in Turkey. [26,34,35]. We conclude that Naegleria spp.…”
Section: Discussionmentioning
confidence: 77%